Biocontrol Efficacy of Trichoderma spp. Against Phytophthora Blight of Pepper - Timila, Ram Devi; Manandhar, Shrinkhala (Nepalese Horticulture, 2020)
Phytophthora blight (PB) caused by Phytophthora capsici Leonian is an economically important disease of pepper in Nepal. Experiments were conducted in epiphytotic conditions at Luvu, Lalitpur where severe outbreak of PB used to occur. The experiment was designed in randomized complete block with three replications. Three isolates of Trichoderma harzianum viz, T. harzianum (T22), T. harzianum (T69), and T. harzianum and one isolate of T. asperellum, were tested for their efficacy under the field conditions compared to chemical fungicides, copper oxychloride and fluazinam for two years, 2012 and 2013. In the first year experiment, the effect of all three isolates of T. harzianum was significantly different from the control. T. harzianum (T69), the local isolate was found better in reducing PB incidence and severity by 46% and 27% respectively during 2012. Similarly, in 2013 PB incidence and severity were reduced by 36% and 42% respectively and yield increased by 57% over control. However the chemical fungicides, fluazinam was the best treatment in reducing PB severity with increased yield by 70% followed by copper oxychloride that increased yield by 62% over control during 2013. There was no significant difference in efficacy of T69 and tested chemical fungicides. Hence, the use of Trichoderma harzianum (T69) could be one of the environmentally sound tools for the integrated management of Phytophthora blight.